2016
DOI: 10.18063/jsc.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Towards smart concrete for smart cities: Recent results and future application of strain-sensing nanocomposites

Abstract: The use of smart technologies combined with city planning have given rise to smart cities, which empower modern urban systems with the efficient tools to cope with growing needs from increasing population sizes. For example, smart sensors are commonly used to improve city operations and management by tracking traffic, monitoring crowds at events, and performance of utility systems and public transportation. Recent advances in nanotechnologies have enabled a new family of sensors, termed self-sensing materials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Smart city initiatives attracted the attention of many researchers and politicians on issues such as mobility, security, environment, or any combination of them, since they are driven by the goal of serving citizens in a better way [1] . Moreover, smart cities facilitate the government to monitor, understand, analyze, and plan the city in order to improve the equity, efficiency, and quality of life [2,3] . The attention of the research activity summarized in this paper is focused on the concept that the smart city development provides opportunities to enhance the quality of civil infrastructures as well.…”
Section: Introductionmentioning
confidence: 99%
“…Smart city initiatives attracted the attention of many researchers and politicians on issues such as mobility, security, environment, or any combination of them, since they are driven by the goal of serving citizens in a better way [1] . Moreover, smart cities facilitate the government to monitor, understand, analyze, and plan the city in order to improve the equity, efficiency, and quality of life [2,3] . The attention of the research activity summarized in this paper is focused on the concept that the smart city development provides opportunities to enhance the quality of civil infrastructures as well.…”
Section: Introductionmentioning
confidence: 99%
“…The variation of strain or stress is associated with the variation in material's electrical characteristics, such as resistance or impedance. Therefore, it is possible to efficiently detect and localize crack formation and propagation in selected concrete element [5]. The concept of smart concrete is based on the idea from the last decade devoted to application of fibers in concretes (FRC -fiber reinforced concrete), which enabled sensing the strain by piezoresistivity or sensing damage by utilizing the relation between damage and electric resistance [6].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the remarkable mechanical and electrical properties of some nanomaterials, which make these nanoparticles ideal for manufacturing self-sensing cement-based composites [5].…”
Section: Introductionmentioning
confidence: 99%
“…With the need to actively monitor the health of large-scale civil infrastructure, there is a need to used with Portland cement are carbon nanotubes [3], [26], [27], carbon fibers [27], [28] and carbon black [15], [18]. Also used are materials like Piezoresistive ceramics [29].…”
Section: Smart Cementitious Materialsmentioning
confidence: 99%
“…D'Alessandro et al [3] modelled a cementitious sensor fabricated with MWCNT's and observed its response to dynamic loading. The cementitious sensors were mounted on a large beam and a dynamic load was applied.…”
Section: Chapter 2: Review Of Existing Literaturementioning
confidence: 99%